Emeraldalicious - Kann, Victoria (New York : Harper, 2013)
Recycling magic turns a garbage-filled park into a "greentastic" garden.
2.3
K-3
Keywords: Recycling (Waste, etc.) -- Juvenile fiction; Green movement -- Juvenile fiction; Magic -- Juvenile fiction; Recycling (Waste) -- Fiction; Green movement -- Fiction; Magic -- Fiction; Recycling -- Fiction; Environmental movement -- Fiction; Magic -- Fiction; Picture books for children